2012
DOI: 10.1007/s10151-012-0862-1
|View full text |Cite
|
Sign up to set email alerts
|

A four-year retrospective study and review of selection criteria and post-operative complications of stapled haemorrhoidopexy

Abstract: With careful selection of patients, PPH may be indicated for prolapsed internal haemorrhoids. More specific national guidelines are required with regard to contraindications to PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Nevertheless, the authors were unable to confirm this as they did not observe the anesthetic effect in the subjects. 9,18 This study showed that stenosis post-SH was 0.5%. It was associated with scar retraction and anal sphincter hypertonia.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, the authors were unable to confirm this as they did not observe the anesthetic effect in the subjects. 9,18 This study showed that stenosis post-SH was 0.5%. It was associated with scar retraction and anal sphincter hypertonia.…”
Section: Discussionmentioning
confidence: 79%
“…8 Shanmugam (2010) found that SH controls second-degree internal hemorrhoid better than RBL in one year with no major complications. Butterworth (2012) reported that only 10% of those who underwent SH were re-admitted due to rectal bleeding, postoperative pain, and urinary retention. Sultan (2014) also found that postoperative bleeding that needed further surgery after SH was 3 to 5%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 12-year follow-up study, the recurrence rate was 40.9% after SH 34 , and in another long-term follow-up study, SH and conventional hemorrhoidectomy have similar rate of additional medical or surgical treatment for recurrence 35 . Many studies have pointed out that patients with grade 2 to 3 hemorrhoidal disease without external prolapsed skin have satisfied therapeutic effect after SH [36][37][38][39] . Kim, et al reported that the recurrence rate is similar in SH and conventional hemorrhoidectomy under appropriate patient selection and resection of excess external prolapsed skin if necessary 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In short, NIR technology is employed to visually assess the vascular sufficiency of a stapled anastomosis intra-operatively after its construction [2,3]. At this time point, patients are simply administered an intravenous injection (1 ml via a peripheral cannula) of a fluorophore with a long track record of safe clinical use (indocyanine green, 2.5 mg/ml).…”
Section: Author Contributionsmentioning
confidence: 99%